The role of the bronchial provocation challenge tests in the diagnosis of exercise-induced bronchoconstriction in elite swimmers - Castricum, A.; Holzer, K.; Brukner, P.; Irving, L. (British Journal of Sports Medicine, 2010)
Background: The International Olympic Committee-Medical Commission (IOC-MC) accepts a number of bronchial provocation tests for the diagnosis of exercise-induced bronchoconstriction (EIB) in elite athletes, none of which have been studied in elite swimmers. With the suggestion of a different pathogenesis involved in the development of EIB in swimmers, there is a possibility that the recommended test for EIB in elite athletes, the eucapnic voluntary hyperpnoea (EVH) challenge, may be missing the diagnosis in elite swimmers.